(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2020)
Illegal migration in Republic of Macedonia but also in Europe has been present since ever as an issue that is subject to regulation in national legislations but also at European level. Still, the issue gains great attention especially with the European migrant crisis from 2015/2016 which stroke the European Union, but also had repercussions upon the states along the Balkan route. Starting from that, the subject of this research paper will tackle Readmission agreements which the EU concludes with third countries that serve as a tool for return of irregular migrants in third countries of origin or transit countries. Concretely, the research will be directed to Readmission agreement between the EU and Republic of Macedonia, where it will be examined if and to what extent the agreement is being implemented by the Republic of Macedonia, both in relation to own country nationals and third country nationals. After having determined the status of its implementation and possible shortcomings, certain suggestions and hypothesis will be given concerning its implementation